SOCIAL INFLUENCE AND E-WALLET BEHAVIORAL INTENTION IN INDONESIA’S DIGITAL PAYMENT ECOSYSTEM - Raissa Anugrah; Endrawati Endrawati; Afridian Wirahadi Ahmad (INSTITUT TEKNOLOGI DAN BISNIS PGRI DEWANTARA JOMBANG, 2026)
Introduction: E-wallet adoption has become a critical issue in Indonesia’s digital financial ecosystem, yet empirical evidence on its behavioral determinants remains inconsistent, particularly among general users in medium-sized cities. This study examines the effects of security, promotion, service features, and social influence on users’ behavioral intention to use e-wallet services in Padang City by extending the Theory of Planned Behavior. Methods: A quantitative explanatory design was employed using a cross-sectional survey. Data were collected from 388 e-wallet users selected through purposive sampling, with respondents required to have used an e-wallet and completed at least two transactions within one month. The data were analyzed using Partial Least Squares Structural Equation Modeling with SmartPLS 4.0. Results: Security, promotion, service features, and social influence positively and significantly affect behavioral intention. The model explains 45.2% of the variance in intention to use, with social influence emerging as the strongest predictor, followed by promotion, service features, and security. Discussion: The findings indicate that e-wallet adoption is shaped by technological assurance, promotional value, service functionality, and social normalization. This study contributes to digital payment adoption literature by demonstrating that behavioral intention is not only driven by individual evaluations of platform attributes but also by socially embedded influences. The results provide practical insights for e-wallet providers to strengthen security communication, value-based promotion, feature development, and community-oriented adoption strategies.